Genetic Diversity and Polymorphism of Eucalyptus L՚He҆r Speciesby ITS Sequence - Al-tememmi, Noor J.; Al-judy, Neamat J.; Al-zubaidi, Labeeb A. (Iraqi Journal of Science, 2024)
Genus Eucalyptus belongs to the family Myrtaceae that consists of more than 700 species, various hybrids and varieties. The majorly distributed species that are grown in Iraq are Eucalyptus alba, E. macarthurii, E. siderophloia and E. camaldulensis, E. tereticornis, E. vicina. Most Eucalyptus species are highly dependent on rainfall, and this is challenged by climatic changes owing to global warming making it difficult to effectively match the availability of mature trees and the market demand, especially for use as power transmission poles. With the widespread availability of other naturally occurring Eucalyptus species, it has become important to determine the genetic diversity and to analyze the phenotypic traits of these species for suitability as power transmission poles. However, the absence of complete genomic data for this plant greatly limits its ability to progress genetically. The goal of this study was to examine the ribosomal RNA gene in Eucalyptus plants and control the sequencing system on a large scale in this species. Samples from plants were used to extract genomic DNA. Detection analysis was performed using PCR methods. Sequence analysis of ribosomal RNA gene was conducted with data analysis. Gel electrophoresis revealed bands of extracted nucleic acid from the ribosomal RNA gene of plants. The ribosomal RNA gene had several transitions and transversion mutations when compared to other globally known ones. Our findings demonstrated that the ribosomal gene developed in this study can be used for detecting the genus of Eucalyptus plants and obtaining 14 species belonging to the genus of the Eucalyptus was registered at the Gene Bank as new species in Iraq.